2022
DOI: 10.1099/jgv.0.001752
|View full text |Cite
|
Sign up to set email alerts
|

A dopamine antagonist, domperidone enhances the replication of an oncolytic adenovirus in human tumour cells

Abstract: Oncolytic adenoviruses (OAds) have attracted much attention as novel anticancer agents. Numerous studies have examined the antitumour effects of combinational use of an OAd and anticancer agents; however, few chemical compounds enhancing OAd infection have been reported. In this study, we screened a food and drug administration (FDA)-approved drug library containing 1134 small chemical compounds to identify chemical compounds that enhance OAd replication in human tumour cells. We found that domperidone, a dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…1 ). OAd-tAIB-Luc has the human telomerase reverse transcriptase (hTERT) promoter-driven E1A gene linked with the E1B gene by the internal ribosome entry site (tAIB) and the cytomegalovirus (CMV) promoter-driven luciferase gene cassette 25 . The previous study demonstrated that OAd containing the same E1 gene expression cassette mediates no apparent cytotoxicity in normal cells 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). OAd-tAIB-Luc has the human telomerase reverse transcriptase (hTERT) promoter-driven E1A gene linked with the E1B gene by the internal ribosome entry site (tAIB) and the cytomegalovirus (CMV) promoter-driven luciferase gene cassette 25 . The previous study demonstrated that OAd containing the same E1 gene expression cassette mediates no apparent cytotoxicity in normal cells 26 .…”
Section: Resultsmentioning
confidence: 99%
“…The CMV promoter-driven firefly luciferase-expressing replication-incompetent Ad5 vector, Ad-L2, was previously produced 48 . The recombinant OAd5 expressing an hTERT promoter-driven Ad5 E1 gene and CMV promoter-driven firefly luciferase gene (OAd-tAIB-Luc) was previously constructed 25 . The determination of virus particle (VP) titers was accomplished according to Maizel et al 49 In vitro luciferase assay.…”
Section: Methodsmentioning
confidence: 99%